PENDAMPINGAN TATA KELOLA ADMINISTRASI UNTUK RUMAH SINGGAH PEDULI (CABANG BANDUNG, JAWA BARAT) - Andina Nur Fathonah; Rachmat Hidayat; Dudi Abdul Hadi; Lilis Maryanti; Nadila Andriana (LPPM Universitas Bina Bangsa, 2024)
This PkM activity is carried out in the short, medium and long term. RSP management must be able to run operational administration properly. Although there are many types of shelters in Bandung, this PkM is specialized in the Bandung Branch of RSP, West Java. Administrative management for Rumah Singgah Peduli is introduced, discussed and applied how the proper techniques in this PkM. A MS.Excel helps in the process of running the administration until a simple financial report of RSP is expected to be able to classify receipts and expenses for each transaction that occurs. The intended object for this PkM is assumed to have less administrative knowledge. This service activity provides guidance and assistance for RSP in improving the information presented in the Non-Profit financial statements. This PkM program is focused on RSP and provides understanding so that it is able to make good records. It is hoped that the management and administration of RSP will have new knowledge related to administration in running their operations and be able to improve the quality of information presented and be professional